The Role of Parents in Shaping Early Childhood Adherence in Implementation of the Health Protocol in Daily Activity - Wijayanti, Yoga Tri (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Covid-19 is a virus SARS-COV-2 corona which causes disease in humans. Based on official government data, 512 children have died due to Covid-19 (Pulungan, 2020). Prevent transmission of the virus by implementing the 5M health protocol. This research aims to determine the determinants of implementing health protocols in early childhood. This research uses an analytical survey design with a cross sectional study approach. The independent variables are knowledge, attitudes and education. Meanwhile, the dependent variable is the implementation of the 5M early childhood health protocol. This research involved 403 early childhood children in TK Alam IT Gladi Insan Cendekia, Metro Barat,, using a checklist to measure children's behavior regarding the implementation of the 5M health protocol. The data obtained were analyzed univariately with percentages, then analyzed bivariately using chi square and continued with multivariate analysis with multiple logistic regression analysis with prediction models. Based on the results of the analysis, all independent variables have an influence on the implementation of early childhood health protocols (p0.05), and parental education is the variable that has the most influence on early childhood behavior in the new normal period (p=0.000, Exp: 7.637).  Keywords: : Role of Parents, 5M Prokes, Early Childhood, COVID-19